Can Worried Parents Predict Effects of Video Games on Their Children? A Case-Control Study of Cognitive Abilities, Addiction Indicators and Wellbeing - Lieberoth, Andreas; Fiskaali, Anne (Frontiers in Psychology, 2021)
Many parents worry over their children’s gaming habits, but to what extent do such worries match possible detrimental effects of excessive gaming? We attempted to answer this question by comparing children of highly concerned parents with other adolescents of the same age. 34 parents who identified as highly concerned over their children’s video game habits were recruited for a public study in collaboration with a national TV station. Using an online experimental platform in conjunction with surveys of parents’ beliefs and attitudes, we compared their children to age-matched peers in an exploratory case-control study. The scores of children with highly concerned parents on tests of cognitive control (cued task-switching and Iowa Gambling Task) and psychological wellbeing (WHO-5) were statistically similar to controls, suggesting no selective cognitive or psychological detriments from gaming or otherwise in the cases with concerned parents. The case group however, did spend more time gaming, and scored higher than controls on problem gaming indicators (Gaming Addiction Scale), which also correlated negatively with wellbeing. Within the case group, wellbeing effects seemed mainly to consist in issues of relaxation and sleep, and related to gaming addiction indicators of playing to forget real-world problems, and the feeling of neglecting non-gaming activities. Where most results of research staged for TV never get published, making it difficult to interpret both methods and results, we here present, this paper describes findings and participant recruitment in detail. The relationship between parental concern and children’s gaming is discussed, as is the merits and challenges of research conducted with media, such as TV programs and their recruited on-screen participants.